(untitled) - Satomi, Kishio (London, 1923)
An introduction to Japanese spiritual civilization,its significance and realization; Nichirenism (the true Mahayana Buddhism) and Japanese national principles.
Keywords: Nichiren, 1222-1282.,Buddha and buddhism,Japan; Civilization